The Effect of Group Counseling on the Knowledge About Delivery in Women Referring to Preconception Care in Comprehensive Health Centers: A Randomized Clinical Trial - Maryam Ghafari Azandarianei; Batoul Khodakarami; Zahra Masoumi; Farideh Kazemi (Hamadan University of Medical Sciences, 2020)
Introduction: Pregnancy and childbirth is one of the most important stages in women's lives. One of the reasons for women's desire to choose interest in cesarean delivery is lack of enough knowledge in choosing the type of delivery. The purpose of this study was to investigate the effect of group counseling on the knowledge about Birth Method in women referring to preconception care.  Methods: The present study is a randomized clinical trial, with a design of two groups (test group and control group), with two stages of pre- and post-test. Sampling was done in a multi-step manner in 2018-2019. 240 women with preconception files were selected randomly from the SIB application of the 8th comprehensive health center of the city of Hamadan. Then, 100 women who met the inclusion criteria were divided into two groups of test and control by assignment sequence. The data collection tool was a questionnaire including demographic and midwifery information, knowledge questions about the methods of delivery. The data were analyzed using SPSS 20. P-value less than 0.05 was considered significant.  Results: Comparison of mean (SD) scores of knowledge in the post-intervention stage indicated that by controlling the effect of pre-test scores, the mean score of knowledge in the intervention group was significantly more than the control group (43.88 (4.85) versus 22.09 (79 / 4)) (P<0.001).  Conclusion: The results of this study showed that group counseling can lead to increased awareness of the choice of natural childbirth. Therefore, by taking advantage of the least possible opportunities in prenatal care for education and counseling, women can be guided to the conscious choice of the type of delivery. Also, the repetition of training and counseling in pregnancy care causes changes in attitudes and performance of women.